1988
DOI: 10.1079/bjn19880083
|View full text |Cite
|
Sign up to set email alerts
|

The digestion of perennial ryegrass (Lolium perenne cv. Melle) and white clover (Trifolium repens cv. Blanca) by grazing cattle

Abstract: I. Pure swards of perennial ryegrass (Loliwn perenne cv. Melle) as a primary growth (May), trimmed primary growth (early June) and regrowth (late June), and white clover (Trifolium repens cv. Blanca) as a mature primary growth (July) and vegetative regrowth (August), were grazed by twelve Friesian steers (mean body-weights throughout experiment 152-231 kg) at daily allocation rates of forage which provided dry matter (DM) intakes ranging from 28 to 36 g/kg body-weight).2. Total nitrogen contents of the three r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
35
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 15 publications
7
35
0
Order By: Relevance
“…However, these microbial proteins provide only 65% of the total protein required for intensive milk production (Leng, 1990). In addition, about 40% of dietary proteins can be lost in the rumen due to microbial degradation (Ulyatt et al, 1988). Hence, ruminant animals also undergo limitation in essential amino acids uptake.…”
Section: Introductionmentioning
confidence: 99%
“…However, these microbial proteins provide only 65% of the total protein required for intensive milk production (Leng, 1990). In addition, about 40% of dietary proteins can be lost in the rumen due to microbial degradation (Ulyatt et al, 1988). Hence, ruminant animals also undergo limitation in essential amino acids uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Red clover is an upright growing plant like alfalfa, whereas the white clover spreads by stolons, which are horizontal above-ground stems. Clover crops generally have a lower content of NDF than grasses and a higher lignification of the cell wall (Ulyatt et al, 1988). Ulyatt et al (1988) found the lowest NDF content in the leaves of white clover.…”
Section: Silagesmentioning
confidence: 99%
“…Clover crops generally have a lower content of NDF than grasses and a higher lignification of the cell wall (Ulyatt et al, 1988). Ulyatt et al (1988) found the lowest NDF content in the leaves of white clover. In the petiole, the content was higher, whereas it increased in the flowers at advancing maturity (Wilman and Altimimi, 1984).…”
Section: Silagesmentioning
confidence: 99%
“…Ulyatt et al (1988) predicted that net losses occur in cattle when diets contain in excess of 25.5 g nitrogen (N)/kg of organic matter (OM) and Beever (1993) suggested that this loss may approach 23-30% of total N intake in lactating cows consuming high quality forages. Despite these losses, the net synthesis of microbial protein in ruminants fed fresh forages can be relatively efficient, although the composition and digestibility of the forage are important moderating factors (SCA 1990).…”
Section: Introductionmentioning
confidence: 99%